Production of Manooligomannan from Palm Kernel Cake by Mannanase Produced from Streptomyces Cyaenus - Purnawan, Awan; Yopi, Yopi; Irawadi, Tun Tedja (Biosaintifika: Journal of Biology & Biology Education, 2017)
The increase of public attention to health has prompted researchers to look for new sources of functional food. Palm Cake Kernel (PKC) waste was abundant in Indonesia, Oligosaccharide has an important benefit for human health. Recently oligosaccharide is not only important as an artificial sweetener, but also as a functional food component. This study was aimed to produce oligo-mannan enzymatically from PKC waste using mannanase derived from of Streptomyces cyaenus isolates of indigenous Indonesia. The enzyme concentration was determined by enzyme activity assay while oligo-mannan content in the PKC was analyzed using TLC and HPLC. Mannanase enzyme activity of 1706 U/ml on the second day of agitation 200 rpm at a temperature of 30C Hydrolysis of mannooligomannan by using mannanase produced by streptomyces cyaenus. The optimum mannanase enzyme activity obtained on day 2 with the value of the activity as much of 0.702 U/mL. The protein content of the 2nd day at an agitation speed of 150 rpm, 200 rpm, and 250 rpm, respectively, were 1783, 1950 and 2283 ppm. Streptomyces cyaenus is Indonesian original isolates potentially producing mannanase that can produce mannooligomannan.